2021
DOI: 10.3390/ijms222112076
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting Antimicrobials from Lactiplantibacillus plantarum: Key Factors Underlying Its Probiotic Action

Abstract: Lactiplantibacillus plantarum (L. plantarum) is a well-studied and versatile species of lactobacilli. It is found in several niches, including human mucosal surfaces, and it is largely employed in the food industry and boasts a millenary tradition of safe use, sharing a long-lasting relationship with humans. L. plantarum is generally recognised as safe and exhibits a strong probiotic character, so that several strains are commercialised as health-promoting supplements and functional food products. For these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 180 publications
(257 reference statements)
1
25
0
Order By: Relevance
“…Lactiplantibacillus plantarum ( Ltp. plantarum ) is a known versatile strain of lactic acid bacteria belonging to the Lactobacilli genus that is often used in the fermentation of foods due to its ability to survive in harsh conditions, and its potential to exhibit probiotic properties [ 10 , 13 ]. Ltp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactiplantibacillus plantarum ( Ltp. plantarum ) is a known versatile strain of lactic acid bacteria belonging to the Lactobacilli genus that is often used in the fermentation of foods due to its ability to survive in harsh conditions, and its potential to exhibit probiotic properties [ 10 , 13 ]. Ltp.…”
Section: Introductionmentioning
confidence: 99%
“…Ltp. plantarum strains are adapted to the human mucosal environment and other ecological niches [ 13 ]. Similarly, Leuconostoc pseudomesenteroides ( Leu pseudomesenteroides ) are lactic acid bacteria belonging to the Leuconostoc genera which have been identified for their antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Although both strains exerted an almost similar spectrum of inhibition, the small difference might be related to the nature of the substances released in the extract and the target pathogen. Early studies demonstrated the inhibitory activity of bacteriocin-like substances from different L. plantarum is species-specific ( Rocchetti et al, 2021 ). Our results were in concordance with our previous results indicating that both the spectrum and the strength of antibacterial property of LAB are strain-specific.…”
Section: Resultsmentioning
confidence: 99%
“…As well, several strains are producing a large group of natural substances such as RiPP-like molecules (ribosomally synthesized and post-translationally modified peptides), PKs (polyketides), NRPs (non-ribosomally produced peptides), terpenes with application in medicine ( Montalbán-López et al, 2021 ). Considering these numerous attributes along with the strains’ flexibility to adapt in several environments make L. plantarum strains an ideal and effective probiotic or antimicrobials producer which might confer positive health benefits to humans ( Fidanza et al, 2021 ; Rocchetti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To map adaptations to carbohydrates that are growth dependent and independent, we systematically compared the response to metabolic stress in microaerophilic (CO 2 enriched environments) >3% CO 2 ) conditions of the five probiotic Lactobacillaceae species: Lacticaseibacillus rhamnosus GG (15), Lacticaseibacillus casei (16), Lactobacillus acidophilus (17), Lacticaseibacillus paracasei , and Lactiplantibacillus plantarum (18) during planktonic growth and colony biofilm formation. Bacillus coagulans , a probiotic Bacilli belonging to the same phylum(19), was studied as a non-Lactobacillaceae LAB control strain.…”
Section: Introductionmentioning
confidence: 99%